Impact of COVID‐19 pandemic on viral hepatitis in Africa: Challenges and way forward. (30th August 2021) - Ismail, Zainab; Aborode, Abdullahi Tunde; Oyeyemi, Ajagbe Abayomi; Khan, Hiba; Hasan, Mohammad Mehedi; Saha, Anwesha; Akah, Blessing
Abstract: With the overwhelming COVID‐19 pandemic in Africa, many other severe epidemics have been given low priority, such as viral hepatitis. Patient mortality due to viral hepatitis has raised concern to COVID‐19 patients due to compromise with undiagnosed hepatitis in Africa. The pandemic has worsened the control of the viral hepatitis epidemic as healthcare control facilities have moved their focus towards curbing COVID‐19 infections. However, different challenges have arisen to viral hepatitis patients because of low health attention that declines the progress of already diagnosed hepatitis patients. Follow‐up plans, routine testing and treatment plans for viral hepatitis are no longer as strict with the human resources transferred towards combating the pandemic. Thus, a global effort is required to abide by renewed recommendations to eradicate viral hepatitis in Africa that also fit the current picture of the COVID‐19 pandemic. The article discusses the current challenges viral hepatitis patients faced during the COVID‐19 pandemic and important recommendations that can see through these challenges in Africa.